Development of Shot Put Learning Media Using Sawdust Material for Grade V Students at Elementary School 003 Loa Janan Ilir, Samarinda City - Andi Alif Tunru; Nurdin Arifin; Lisa Handayani; Rahmat Ilahi; Rachmat Hidayat; Musdalifah Ramli (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2025)
The development of shot put learning media using sawdust as the base material represents an innovative approach in physical education aimed at addressing the limitations of shot put learning facilities and infrastructure in schools, particularly for elementary students. This study aims to provide a practical solution to the shortage of equipment in elementary schools and to enhance teachers' creativity in designing learning media that is affordable, easily accessible, and safe for students to use. The research employed a Research and Development (R&D) ADDIE model, which includes the stages of needs analysis, design, development, testing, and evaluation. Data were collected through observations, questionnaires, interviews, and student learning outcome tests conducted before and after the implementation of the media. Data analysis involved descriptive statistics and paired t-tests to measure the effectiveness of the sawdust-based shot put learning media on Grade V students at Elemntary School 003 Loa Janan Ilir. The study’s findings are as follows: 1) The media was developed using the ADDIE model (Analysis, Design, Development, Implementation, Evaluation) and proved effective in improving student learning outcomes, 2) The average post-test score significantly increased from 60.5 to 85.3 after using the media, indicating enhanced student understanding and skills, 3) The media was designed using lightweight, inexpensive, and environmentally friendly sawdust, replacing the standard shot put equipment, which is heavy and limited in number, thereby facilitating safe and enjoyable practice of basic shot put techniques, 4) Expert validation of content and media yielded an average feasibility score of 86%, with physical aspects, content relevance, and usability rated as safe, curriculum-aligned, and user-friendly for both teachers and students. Furthermore, the media fosters an active and inclusive classroom environment, boosting student motivation and participation in physical education learning.